2016
DOI: 10.1159/000443797
|View full text |Cite
|
Sign up to set email alerts
|

Association of FEF25-75% Impairment with Bronchial Hyperresponsiveness and Airway Inflammation in Subjects with Asthma-Like Symptoms

Abstract: Background: Forced expiratory flow at 25 and 75% of the pulmonary volume (FEF25-75%) might be considered as a marker of early airway obstruction. FEF25-75% impairment might suggest earlier asthma recognition in symptomatic subjects even in the absence of other abnormal spirometry values. Objectives: The study was designed in order to verify whether FEF25-75% impairment in a cohort of subjects with asthma-like symptoms could be associated with the risk of bronchial hyperresponsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Early airway obstruction group (n = 26, normal FEV 1 and FEV 1 /FVC, but Forced expiratory flow over the middle half of the FVC (FEF 25-75% ) <65% of predicted) [23];…”
Section: Methodsmentioning
confidence: 99%
“…Early airway obstruction group (n = 26, normal FEV 1 and FEV 1 /FVC, but Forced expiratory flow over the middle half of the FVC (FEF 25-75% ) <65% of predicted) [23];…”
Section: Methodsmentioning
confidence: 99%
“…FEF 25-75% is the most sensitive measure of airflow in peripheral airways where primary airflow obstruction originates, 7 and it is reduced in early bronchial impairment, which is associated with small airway disease. [8][9][10][11] Airway remodeling, mucus plugging, and immune cell infiltration induced by cigarette smoking ultimately result in small airway disease, which is a cardinal feature of COPD. 12 Some researchers have found that decreased FEF 25-75% is frequently observed in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“… Although the use of MMEF has been criticized for the failure to contribute to clinical decision-making 34 , we found that MMEF correlated significantly with various clinical variables and that the coefficient of variation for two acceptable maneuvers was small. Furthermore, the usefulness of MMEF in terms of correlation with airway hyperresponsiveness and inflammation in asthma 35 36 and asthma-like symptoms 37 has been demonstrated. Despite different settings, it is still likely that MMEF% predicted would have clinical significance to guide severity assessment of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the usefulness of MMEF in terms of correlation with airway hyperresponsiveness and inflammation in asthma3536 and asthma-like symptoms37 has been demonstrated. Despite different settings, it is still likely that MMEF% predicted would have clinical significance to guide severity assessment of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%